The significance of Anomalocaris and other Radiodonta for understanding paleoecology and evolution during the Cambrian explosion - Potin, Gaëtan J.-M.; Daley, Allison C. (Frontiers in Earth Science, 2023)
One of the most widespread and diverse animal groups of the Cambrian Explosion is a clade of stem lineage arthropods known as Radiodonta, which lived exclusively in the early Paleozoic. First reported in 1892 with Anomalocaris canadensis, radiodonts are now one of the best known early animal groups with excellent representation in the fossil record, and are ubiquitous components of Konservat-Lagerstätten from the Cambrian and the Early Ordovician. These large swimmers were characterised by a segmented body bearing laterally-oriented flaps, and a head with a distinct radial oral cone, a pair of large frontal appendages adapted for different feeding modes, compound eyes on stalks, and prominent head carapaces. Radiodonts inform on the paleoecology of early animal communities and the steps involved in euarthropod evolution. Four families within Radiodonta have been established. The raptorial predator families Anomalocarididae and Amplectobeluidae were dominant early in the evolutionary history of Radiodonta, but were later overtaken by the mega-diverse and widespread Hurdiidae, which has a more generalised sediment-sifting predatory mode. Suspension feeding, notably in the families Tamisiocarididae and Hurdiidae, also evolved at least twice in the history of the clade. The well-preserved anatomical features of the radiodont body and head have also provided insights into the evolution of characteristic features of Euarthropoda, such as the biramous limbs, compound eyes, and organisation of the head. With 37 species recovered from all major paleocontinents of the Cambrian and Early Ordovician, Radiodonta provides a unique opportunity for revealing evolutionary patterns during the Cambrian Explosion.